ASSESSMENT OF THE STRUCTURAL INTEGRITY OF THE JAKARTA . CIKAMPEK TOLL ROAD PAVEMENT - Suwendi
ASSESSMENT OF TTIE STRUCTURAL INTEGRITY OF THE JAKARTA - CIKAMPEK TOLL ROAD PAVEMENT, Suwendi, 1995, Program Magister Sistem dan Teknik Jalan Raya, Program Pascasarjana, Institut Teknologi Bandung. The proportion of the road network in Indonesia year by year increases both in volume and in quality. After a road has been opened and subjected to use its serviceability will decrease to a minimum acceptable level. During and after its service life a road needs maintenance and strengthening. This research has been concerned with the methods used to evaluate the integrity of the road structures, and has involved analysing traffic loading, choosing overlay and deflection models, and assessing pavement structural integrity from the effect of traffic loading, the chosen overlay and deflection model. The road chosen for the study was the Jakarta-Cikampek Toll Road for which a traffic assignment model was established. With the traffic assignment model traffic loading was distributed accurately into the toll road network. The traffic analysis showed that traffic growth on the Jakarta-Cikampek Toll Road, over the period 1989 - 1994, was on average greater than 20 % per year. The predicted cumulative traffic loading on some links, over the period 1994 - 2000, were found to vary from 5 msa for the fast lane normal case to 200 msa for the slow lane overloading case. Axle loadings were assessed using the Weigh-in-Motion method. The deflection and overlay models proposed by the Asphalt Institute, Bina Marga, HRODI & ACODI, and NAASRA were examined. It was concluded that the Bina Marga deflection model (BMC'83) and the ACODI (CGRA'65) overlay model with equivalency factor (EF) = 2 were the most appropriate. Because the ACODI method has been widely used in Indonesia, a comparison of this method with the Bina Marga and DAMA methods was made for overlay calculations. It was found that the remaining life of pavement varied from about 1 msa to 100 msa, whether calculated using the Bina Marga method or program DAMA. In general the Bina Marga method gave greater remaining life than program DAMA. Critical pavement life was found to be based on the program DAMA (with a two layer system) vertical strain component on the top of the subgrade. It thus seems that the compressive strain on the top of the subgrade (DAMA) is more critical than deflection criterion (Bina Marga); further research is needed with treatment of the existing pavement as a 3 layer system rather than 2 layer. The analysis indicated overlay requirements of 0 to 200 mm (Bina Marga), from 25 to 230 mm (ACODI), and from 25 to 340 mm (DAMA). In general the Bina Marga indicated the thinnest overlay requirements, program DAMA the thickest, and ACODI in between. Using program DAMA (three layer system), the critical pavement design life was found to depend on the tensile strain underneath the bituminous overlay layer and this was more critical than the Bina Marga deflection criterion; this serves to show the need for further research involving treatment of the existing pavement as a 3 layer system (4 layer system after overlay). It was found that the effect of applying a temperature correction to the surfacing layer was significant for both remaining pavement life and overlay calculations. Research should be directed to develop pertinent temperature correction factors. Finally, the effect of reducing the thickness of overlay required for a given situation due to a shortage of budget has been shown to have a significantly harmful effect on pavement life